Potential Alzheimer’s Disease Therapeutics Among Weak Cysteine Protease Inhibitors Exhibit Mechanistic Differences Regarding Extent of Cathepsin B Up-Regulation and Ability to Block Calpain - Romine, Heather; Rentschler, Katherine M.; Smith, Kaitlan; Edwards, Ayanna; Colvin, Camille; Farizatto, Karen; Pait, Morgan C.; Butler, David; Bahr, Ben A. (European Scientific Journal, ESJ, 2017)
Cysteine protease inhibitors have long been part of drug discovery programs for Alzheimer’s disease (AD), traumatic brain injury (TBI), and other disorders. Select inhibitors reduce accumulating proteins and AD pathology in mouse models. One such compound, Z-Phe-Aladiazomethylketone (PADK), exhibits a very weak IC50 (9-11 μM) towards cathepsin B (CatB), but curiously PADK causes marked up-regulation of the Aβ-degrading CatB and improves spatial memory. Potential therapeutic and weak inhibitor E64d (14 μM IC50) also up-regulates CatB. PADK and E64d were compared regarding the blockage of calcium-induced cytoskeletal deterioration in brain samples, monitoring the 150-kDa spectrin breakdown product (SBDP) known to be produced by calpain. PADK had little to no effect on SBDP production at 10-100 μM. In contrast, E64d caused a dosedependent decline in SBDP levels with an IC50 of 3-6 μM, closely matching its reported potency for inhibiting μ-calpain. Calpain also cleaves the cytoskeletal organizing protein gephyrin, producing 49-kDa (GnBDP49) and 18-kDa (GnBDP18) breakdown products. PADK had no apparent effect on calcium-induced gephyrin fragments whereas E64d blocked their production. E64d also protected the parent gephyrin in correspondence with reduced BDP levels. The findings of this study indicate that PADK’s positive and selective effects on CatB are consistent with human studies showing exercise elevates CatB and such elevation correlates with improved memory. On the other hand, E64d exhibits both marginal CatB enhancement and potent calpain inhibition. This dual effect may be beneficial for treating AD. Alternatively, the potent action on calpain-related pathology may explain E64d’s protection in AD and TBI models.